2006
DOI: 10.1186/1472-6963-6-72
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomized educational intervention to reduce inappropriate prescription patterns for elderly patients in general practice – The Prescription Peer Academic Detailing (Rx-PAD) study [NCT00281450]

Abstract: Background: Age-related alterations in metabolism and excretion of medications increase the risk of adverse drug events in the elderly. Inappropriate polypharmacy and prescription practice entails increased burdens of impaired quality of life and drug related morbidity and mortality. The main objective of this trial is to evaluate effects of a tailored educational intervention towards general practitioners (GPs) aimed at supporting the implementation of a safer drug prescribing practice for elderly patients ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 52 publications
0
36
0
13
Order By: Relevance
“…The study intervention consisted of an educational package on safer prescribing practice for older patients. 26 The control groups were assigned to another educational intervention targeting antibiotic prescribing practice for respiratory tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…The study intervention consisted of an educational package on safer prescribing practice for older patients. 26 The control groups were assigned to another educational intervention targeting antibiotic prescribing practice for respiratory tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Reaching these goals by regulatory or other interventions in BZD-Z in the elderly shows variable results. [22][23][24][25] However, there are substantial differences between the health systems in the countries. In Norway the general practitioner scheme which defines a regular physician for each patient and hence continuity in the treatment, provides a good possibility to a close follow up of the BZD-Z users.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway the general practitioner scheme which defines a regular physician for each patient and hence continuity in the treatment, provides a good possibility to a close follow up of the BZD-Z users. 25,26 A third option is to re-evaluate the guidelines and the purpose of guidelines. Studies have shown that, on the whole, BZD-Z are effective and remarkably safe drugs.…”
Section: Discussionmentioning
confidence: 99%
“…9,25,26 A limited number of Our results are consistent with 2 randomized controlled trials published since the start of the OPTI-SCRIPT study in finding a multifaceted intervention to be effective. 13,14 In the Rx-PAD study, Rognstad et al 14 and Straand et al 29 found peer academic detailing, delivered at continuing medical education meetings, with mailed prescriber feedback, produced a 10% (95% CI, 5.9%-15.0%) reduction in PIP. Bregnhøj et al 13 found interactive educational meetings and feedback resulted in a 5-point (95% CI, 7.3-to 2.6-point) improvement in the medication appropriateness index score.…”
Section: Main Findingsmentioning
confidence: 99%